Design and Optimization of IPMSM for Enhanced Efficiency, Cost Reduction, and Performance in Light Electric Vehicles - Kevser Ozer; Murat Yilmaz (IEEE Access)
Light electric vehicles (LEVs) offer environmentally friendly solutions to challenges in sustainable transport, zero emissions, noise reduction, and parking. Among the various motor types, interior permanent magnet synchronous motors (IPMSMs) are the most commonly used in LEVs with belt-drive systems due to their high-power density and efficiency. The main disadvantages of IPMSMs are torque ripple, which can cause noise and vibration, and the cost and availability of the permanent magnets (PMs), which are particularly crucial for LEVs. In this study, the requirements and dimensions of the IPMSM have been determined through analytical analyses and experimental studies of the motor used in a commercial two-wheeled LEV. Electromagnetic analyses were performed to evaluate four magnet configurations—V-shape, U-shape, double V-shape, and double I-shape—leading to the selection of the double I-shape arrangement for its superior performance. Optimization studies, guided by defined cost functions, were then carried out using ANSYS OptiSlang to enhance the motor’s design and overall efficiency. The designed IPMSM achieved a 1.4% improvement in efficiency compared to the commercially used motor, with an expanded high-efficiency operating region on the efficiency map and a 2% reduction in torque ripple. Additionally, the motor cost was reduced by 13% through a 22% increase in reluctance torque and a 12% decrease in magnet quantity. Thus, the cost of this cargo-purpose LEV, which is sold in thousands of units per year, has been reduced by 2.7%, while its range has been increased by 2.3% using the WLTC Class-1 drive cycle through the expanded efficiency map. In addition, compared to the delta-type reference PM rotor geometry, the double-I structure enhances manufacturability while maintaining comparable thermal performance.